PENGARUH BUDAYA ORGANISASI, MOTIVASI DAN KOMPENTENSI TERHADAP KINERJA ASN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING DI POLRES SITUBONDO - Novie Wijayanto; Lusiana Tulhusnah; Siti Soeliha (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The purpose of this study is to analyze the influence of variablesThe Influence of Organizational Culture, Motivation, and Competence on ASN Performance Through Job Satisfaction as an Intervening Variable at the Situbondo Police. Using the Partial Least Square (PLS) Structural Equation Model. Results of direct influence hypothesis testing using the Smart PLS 3.0 application Organizational culture has a significant positive effect on ASN job satisfaction, Motivation has a positive but not significant effect on ASN job satisfaction, Competence has a significant positive effect on ASN job satisfaction, Organizational culture has a significant positive effect on ASN performance, Motivation has a significant positive effect on ASN performance, Competence has a significant positive effect on ASN performance, ASN job satisfaction has a significant positive effect on ASN performance, Organizational culture has a positive but not significant effect on ASN performance through ASN job satisfaction, Motivation has a positive but not significant effect on ASN performance through ASN job satisfaction, and Competence has a significant positive effect on ASN performance through ASN job satisfaction.